COMPARATIVE STUDY ON THE UNDERSTANDING OF RESPONSIVENESS IN PRE-SERVICE PRESCHOOL TEACHERS IN THE COVID-19 EMERGENCY SITUATION (2018-2020) - Jurgena, Inese; Cēdere, Dagnija; Keviša, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The global pandemic of Civid-19 has led to significant changes in the transformation of the system of education and teacher training. Regarding the training of prospective preschool teachers at the institutions of higher education, there is a growing need to develop multiple competencies so that a teacher can create an emotionally safe and supervised learning environment. Our study highlights the importance of the responsiveness of preschool teachers in providing supportive responses, responsibility, and guidance regulating children’s emotions in the pedagogical activity. The aim of the study is to analyze and compare the perceptions of students, pre-service preschool teachers, on teachers’ emotional responsiveness before the global pandemic and during the Covid-19 emergency. The materials and methods used in the study include the theoretical method – the analysis of literature - and the empirical method – a survey of 600 part-time students working in pre-school educational institutions in 2018 and in 2020. The survey was conducted online. The data were processed using the software SPSS. The results of the study demonstrate that, generally, the Covid-19 emergency has increased the willingness of prospective preschool teachers to undertake responsibility and leadership in regulating children’s emotions. The students have become more responsible and determined; their understanding of the importance of emotional responsiveness in teacher’s work is higher than before the pandemic